STRATEGI BERSEPAKAT ANGGOTA-ANGGOTA MASYARAKAT LOKAL DALAM MERESPONS PROGRAM CSR PERUSAHAAN TAMBANG TUMPANG PITU DI BANYUWANGI - GINANJAR PRASTYANTO (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2022)
In the current era, the development of the mining industry is in direct confrontation with members of the community, who first live near the site, which will be mined. In this case, unlike in the New Order era, in the current era, local members have the freedom to oppose development around where they live. It is also experienced by the company who want to open gold mining, in the mountains Tumpang Pitu, Pesanggaran, Banyuwangi. The company's efforts are opposed by members of the local community. Gaining opposition from local community members, the mining company responded by running corporate social responsibility (CSR) programs. However, in response to the offer of CSR programs of the company, the community members responded in the form of a fight over to gain agree among themselves, ie between CSR refusers and CSR recipients. The CSR refusalists wish that members of society who receive CSR abandon their choice of attitude and move on in their footsteps. Meanwhile, the CSR recipients wish that CSR's refusers will allow themselves to determine their will. Therefore, this thesis focuses on finding the answers to the following questions: "how are the strategies of be agree operated by each party of the community members, ie between CSR refusers and CSR recipients, in response to CSR programs of mining companies". This research uses qualitative method. The research scope is Pancer sub-village and Silirbaru sub-village, Sumber Agung village, which is the area where the mining company was founded. The unit of analysis of this research is the language used by members of local communities, both who refuse CSR or recaive CSR in both sub-villages. Methods of collecting data in this study using in-depth interview techniques. Methods of data processing, using restory techniques. And, method of data analysis using thick description. The results of the field findings indicate that in a battle with each other, each party, members of the community use certain discourses. The CSR refusers use the "pro-contra mining" discourse in operating the strategy of be agree to the recipients of the CSR, while the latter uses the discourse of "national people-counter people" and "economic responsibility" in operating behind the strategy of be agree to the party First of all. In operating the strategy of be agree itself, the CSR refusers applies the panopticon technique, ie, total oversight of the CSR recipients. In addition, applying total control, the CSR refusers also uses interpellation techniques. In this case, the CSR refusers operates a total interpellation to the CSR recipients. The effect of the panopticon technique makes CSR recipients experience a self-control situation. To that end, when the position has been pressed, CSR recipients interpellate CSR refusers with the discourse of "national people-counter people" and the discourse of "economic responsibility". The result, they run coexistently.